Challenging Hegemonic Masculinity: The Resistance of Black Woman Battalion in The Six Triple Eight (2024) Film - Za'imah Afifah Marzuqah; Thohiriyah (Rainbow: Journal of Literature, Linguistics and Culture Studies, 2026)
This study examines the portrayal of hegemonic masculinity and the forms of resistance demonstrated by the all-Black women’s 6888th Battalion in the film The Six Triple Eight (2024) by Tyler Perry. This research focuses on the analysis of hegemonic masculinity, which perpetuates discrimination and marginalization within the gender hierarchy experienced by the 6888th Battalion. Primary data were collected from selected scenes in The Six Triple Eight (2024), including dialogue, character interactions, and visual representations related to hegemonic masculinity in the military. The data were analyzed using a descriptive qualitative approach that focuses on the narrative and visual elements of selected scenes, adopting Connell’s concept of hegemonic masculinity as a theoretical framework to interpret the findings. The findings reveal that hegemonic masculinity is reproduced through interconnected institutional practices, including unequal assumptions regarding competence, institutional surveillance, unequal institutional support, and the denial of female authority within the military. The film also portrays the resistance of the 6888th Battalion through professionalism, discipline, and collective solidarity, which challenge these institutional mechanisms. This study contributes to discussions of gender and military representation by demonstrating how hegemonic masculinity is maintained and contested through institutional practices in the film, extending previous studies that primarily emphasize intersectional discrimination.